Respuesta :

cdbuck
These problems are called literal equations(just so you know)
S=L-rL
First, you subtract L from both sides:
S-L=-rL
The commutative property of multiplication states that you can change the order of 2 different numbers being multiplied together and still keep the equation/expression equivalent to the first. We can change r and L around like this:
S-L=-Lr
now we divide both sides by -L:
[tex] \frac{S-L}{-L} =r[/tex]
We can still simplify this, though, by splitting up the fraction on the left:
[tex] \frac{S}{-L} - \frac{L}{-L} =r[/tex]
which is equal to:
[tex] \frac{S}{-L} -(-1)=r[/tex]
for the final step, the double negative becomes a positive:
[tex] \frac{S}{-L} +1=r[/tex]
there is the final simplified answer for r